Initiation and progression of α-synuclein pathology in Parkinson’s disease - Tofaris, GK (Springer, 2022)
α-Synuclein aggregation is a critical molecular process that underpins the pathogenesis of Parkinson’s disease. Aggregates may originate at synaptic terminals as a consequence of aberrant interactions between α-synuclein and lipids or evasion of proteostatic defences. The nature of these interactions is likely to influence the emergence of conformers or strains that in turn could explain the clinical heterogeneity of Parkinson’s disease and related α-synucleinopathies. For neurodegeneration to occur, α-synuclein assemblies need to exhibit seeding competency, i.e. ability to template further aggregation, and toxicity which is at least partly mediated by interference with synaptic vesicle or organelle homeostasis. Given the dynamic and reversible conformational plasticity of α-synuclein, it is possible that seeding competency and cellular toxicity are mediated by assemblies of different structure or size along this continuum. It is currently unknown which α-synuclein assemblies are the most relevant to the human condition but recent advances in the cryo-electron microscopic characterisation of brain-derived fibrils and their assessment in stem cell derived and animal models are likely to facilitate the development of precision therapies or biomarkers. This review summarises the main principles of α-synuclein aggregate initiation and propagation in model systems, and their relevance to clinical translation.